تنازع الاختصاص في القضاء العسكري العراقي - عباس، شاهين احمد; عبدالله، ياسر محمد Abdullah, Yasser Mohammed; الزبيدي، محمد عباس حمودي Hamoudi, Mohammed Abbas (جامعة كركوك - كلية القانون والعلوم السياسية, 2015)
There is no doubt that military jurisdiction contend has its own concept and distinctive nature and is not just the someone, but it is on kinds like qualitative, personal and spatial, and in the nature of reality will accompany the jurisdiction of this type eliminate overlap and conflicts among the military courts themselves or between them and the regular criminal courts, and this conflict comes in tow forms: positive and negative from. their for must find appropriate solutions to the aforementioned things in order to get close to a serious effort in the end justice possible.
لا شك أن اختصاص القضاء العسكري له مفهومه الخاص وطبيعته المتميزة ولا يكون على شاكلة واحدة بل يكون على أنواع وهي النوعي والشخصي والمكاني، وبطبيعة الواع سيصاحب اختصاص هذا القضاء نوع من التداخل والتنازع فيما بين المحاكم العسكرية نفسها أو بينها وبين المحاكم الجزائية العادية، وهذا التنازع يأتي بصورتين الصورة الإيجابية والصورة السلبية لذا ينبغي إيجاد الحلول المناسبة للأمور أنفة الذكر بهدف التقرب من جادة العدالة جهد الإمكان.
Keywords: القوانين والتشريعات -- الاختصاصات القضائية -- القضاء العسكري -- العراق